SOMATIC AND PSYCHIATRIC MORBIDITY OF ELDERLY DRIVERS KILLED IN MOTOR VEHICLE ACCIDENTS IN FINLAND DURING 22-YEAR FOLLOW-UP - JENNY TYNI, PIRKKO RIIPINEN, HELINÄ HAKKO, NIINA SIHVOLA, LIISA KANTOJÄRVI (Psychiatria Fennica)
ABSTRACT Background: The proportion of elderly drivers is increasing, and they have an increased risk of traffic accidents and traffic death. The increased risk has been associated with health problems such as cardiovascular disease and a decline in other key factors related to safe driving that also affect healthy elderly drivers. Materials and methods: We used data from three nationwide registers (Register of road and off-road accidents investigated by Finnish Road Accident Investigation Teams, Care Registers for Health Care and Cause of death register) to analyse somatic and psychiatric morbidity associated with fatal motor vehicle accidents (FMVA) involving elderly drivers in Finland. Deceased elderly drivers were divided into three age groups (65-74 years, 75-84 years and 85 years or over), and we analysed the prevalence of hospital-diagnosed diseases, sociodemographic and other factors affecting the ability to drive at the time of FMVA between these groups. Results: Elderly drivers accounted for almost one fifth (17.2%) of all driver deaths in FMVAs in Finland between 1990–2011. 89.2% of these deaths involved male drivers. Among the oldest, diseases of the circulatory system were most common. The diseases of the nervous system and driving under the influence of alcohol were most common among the younger group. Differences between age groups of elderly drivers, concerning morbidity and other variables studied, were emphasized. Conclusions: Our findings highlight the need for further attention on variation between different age groups of elderly drivers when evaluating fitness to drive.